Au-Doped intermetallic Pd3Pb wavy nanowires as highly efficient electrocatalysts toward the oxygen reduction reaction. Issue 39 (3rd September 2020) - Luo, Sai; Xu, Dazhe; Li, Junjie; Huang, Yuxuan; Li, Lei; Li, Xiao; Wu, Xingqiao; Gao, Mingxi; Yang, Deren; Zhang, Hui
Abstract : Au-Doped intermetallic Pd3 Pb wavy nanowires were synthesized and exhibited substantially enhanced properties for the oxygen reduction reaction relative to commercial Pt/C. Abstract : Developing high-performance non-Pt electrocatalysts toward the oxygen reduction reaction (ORR) is highly desirable but still challenging for industrial application in fuel cells. Here, we report a facile approach for the synthesis of Au-doped Pd3 Pb wavy nanowires (WNWs) with different amounts of Au. We found that the oriented attachment dictated the formation of the WNWs. Such WNWs with several attractive features including a high density of defects, anisotropic one-dimensional nanostructures, ordered intermetallic structures, and Au doping exhibited substantially enhanced catalytic properties in terms of activity and durability towards the ORR in alkaline media compared to commercial Pt/C. Interestingly, the Au doped Pd3 Pb WNWs showed a volcano-like relationship in ORR activity as a function of the amount of Au with the 2% Au-doped Pd3 Pb WNWs being the best ORR electrocatalysts. Specifically, the 2% Au doped Pd3 Pb WNWs achieved the highest mass activity (0.75 mA μg −1 ) at 0.9 V, which was 1.25 and 7.5 times higher than that of the Pd3 Pb WNWs and commercial Pt/C, respectively. More importantly, the 2% Au-doped Pd3 Pb WNWs displayed higher durability with only 22.7% loss in mass activity after 10 000 cycles compared to the commercial Pt/C (38% loss in mass activity) due to their chemically stable intermetallic structures and the effect of Au doping.